S2k Guidlines for Diverticular Disease and Diverticulitis: Diagnosis, Classification, and Therapy for the Radiologist - Schreyer, A. G.; Layer, G. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Diverticular disease and diverticulitis represent an increasingly common disease especially in patients with advanced age. The German Society of Digestive and Metabolic Diseases (DGVS) as well as the German Society of General and Visceral Surgery (DGAV) in collaboration with the German Radiology Society (DRG) created and published S2k guidelines regarding this topic. Knowledge of the diagnosis and therapy of this common disease is extremely important for the radiologist for the daily clinical routine. In this article we review and discuss the most important clinical situations and algorithms of this disease focusing on radiological topics. Additionally, we introduce the new CCD (classification of diverticular disease) system regarding radiology.Key Points:• For the diagnosis of a diverticular disease a sectional imaging method should be performed. First choice should be a „qualified ultrasound examination“ followed by CT in uncertain situations or complicated disease.• Disease classification should be done according the new CCD (Classification of diverticular disease) algorithm.• Based on this new CCD patients can be stratified into outpatient, in-house patient and surgical treatment therapy.Citation Format:• Schreyer AG, Layer G. S2k Guidlines for Diverticular Disease and Diverticulitis: Diagnosis, Classification, and Therapy for the Radiologist. Fortschr Röntgenstr 2015; 187: 676 – 684
Keywords: abdomen; CT; MR imaging; inflammation